Analisis Penerimaan Teknologi IPTV (Studi Kasus Groovia Tv di Kota Semarang) - Noora Qotrun Nada (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
The growth of IPTV technology in Indonesia, particularly in Semarang, doesn’t expand significantly comparing to overseas developements. Therefore, a research about the causes of underdeveloping IPTV technology acceptance is needed. One of PT Telkom’s products that utilized IPTV technology is Groovia TV. In providing Groovia TV service, PT Telkom has improved the networking performance, using this attempt to increase the revenues through triple play, phone/voices, datas and multimedias, however Groovia TV’s customers hasn’t been significant. This thesis analyzes the acceptance of IPTV technology with study case of groovia TV in Semarang. Model that has been used is based on TAM (Technology Acceptance Model) model and analyzed with SEM (Structural Equaion Modelling). This research took a random sampling of the population in Semarang with the speedy customer that had been using Groovia TV, either they still actively use it or has stopped.The research was conducted on February 2013. The results showed that Attitude Toward IPTV (ATT) and perceived of usefulnee (PU) would influence the Intention to Use (IU). Perceived of ease of use (PEU), perceived of enjoyment, and perceived of quality (PQ) will affect ATT as well. Normative pressure (NP) and Price Level (PL) has no direct influence on IU. Customer wishes to use TV Groovia is influenced by perceptions of service quality, perceived preferences, ease of use and benefits obtained, so for PT Telkom as the provider, those four things should be the main concern, especially Groovia TV is running with substantial bandwidth, therefore , the network accesst must be reliable.